(untitled) (Research, Society and Development, 2025)
Antiretroviral therapy (ART) has greatly enhanced the quality of life and life expectancy of people living with HIV. However, concerns about the genotoxic potential of nucleoside reverse transcriptase inhibitors (NRTIs), particularly zidovudine (AZT) and lamivudine (3TC), remain relevant. This study aimed to evaluate the genotoxic effects of AZT, 3TC, and their combination (2:1 ratio) in CHO-K1 cells using the alkaline comet assay. A quantitative laboratory research was carried out. Cells were exposed to increasing concentrations of each drug individually and in combination for 24 hours. DNA damage was quantified as the percentage of DNA in the comet tail. AZT significantly increased DNA damage at the two highest concentrations (900 and 1350 µM), while 3TC did not induce genotoxic effects at any concentration tested. The AZT+3TC combination caused significant DNA damage at the two highest doses compared to the negative control, with no evidence of synergistic interaction relative to AZT alone. These findings align with previous studies and highlight the importance of evaluating DNA integrity in ART regimens. The comet assay proved to be a sensitive tool for detecting NRTI-induced genotoxicity, and the data underscore the need for continued monitoring of combination therapies to ensure long-term treatment safety.